Edición y comentario de los ‘títulos’ Amicitia, Amor y Gloria del florilegio temático contenido en el ms. 246 de la Biblioteca de Santa Cruz de Valladolid - Villalba de la Güida, Israel; Arenal Barrantes, Isabel; Medina López-lucendo, Cecilia (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
The present work focuses on the critical edition of the three ‘titles’ – Amicitia, Amor and Gloria– belonging to the thematic florilegium conserved in the ms. 246 the Old Fund of Valladolid University (Santa Cruz Library), whose probable author is Don Cristóbal García Guillén de la Paz (17th century). The text offers two commentaries: the first one consists on a commentary of works, authors and original texts; the second is a philological commentary on the florilegium. Finally, the philological commentary studies the existence of false attributions and auctores incerti.